An Analysis of water Management and Consumption in Residential, Industrial and Commercial area of Katraj Sukhsagar Nagar, Pune, Maharashtra - Dr. Shalini M. Guldeokar, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Water is one of the most precious natural resources and key elements in the Socio-economic development of a country. A person can live without food for days but cannot survive without water. Water is the basic and fundamental needs of any living being, but sadly this basic need is very soon nearing its end. Water is used for drinking, bathing, and cooking, washing, irrigation and in the industry etc. About 70% earth surface is covered with water but only little fraction of total water available on the earth, which is useful for human consumption it means only 3% water is available to us as fresh water out of this 2.99% is locked up in the mountain or glacier. Only 0.10% fresh water is easily available to us in the form of groundwater. Hence whatever water is available on the earth surface that water we have to conserve otherwise in future we will face water crises. Similarly in this paper had tried to explain how water Management has been co-relates between residential, industrial and commercial point of view. For the present study Katraj Sukhsagar Nagar area has been identified, because in the year 1997, 37 villages have been attached into Pune Municipal Corporation due to this population of Katraj had increased and it’s affected on distribution of water. Hence we should take care of using water to its proper utility and also take care of rain water harvesting method to overcome the scarcity of fresh water in all the sectors like domestic industrial and agriculture. Water is one of the most precious natural resources and key elements in the Socio-economic development of a country. A person can live without food for days but cannot survive without water. Water is the basic and fundamental needs of any living being, but sadly this basic need is very soon nearing its end. Water is used for drinking, bathing, and cooking, washing, irrigation and in the industry etc. About 70% earth surface is covered with water but only little fraction of total water available on the earth, which is useful for human consumption it means only 3% water is available to us as fresh water out of this 2.99% is locked up in the mountain or glacier. Only 0.10% fresh water is easily available to us in the form of groundwater. Hence whatever water is available on the earth surface that water we have to conserve otherwise in future we will face water crises. Similarly in this paper had tried to explain how water Management has been co-relates between residential, industrial and commercial point of view. For the present study Katraj Sukhsagar Nagar area has been identified, because in the year 1997, 37 villages have been attached into Pune Municipal Corporation due to this population of Katraj had increased and it’s affected on distribution of water. Hence we should take care of using water to its proper utility and also take care of rain water harvesting method to overcome the scarcity of fresh water in all the sectors like domestic industrial and agriculture